Analisis Waktu Tempuh Kendaraan Bermotor Dengan Metode Kendaraan Bergerak (Studi Kasus Jalan Pekanbaru - Bangkinang) - Zul Andri; Horas. SM Marpaung; Mardani Sebayang (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Travel time estimation is one of the parameters to predict a journey for traveler who want to travel. The travel time in this research using Moving Observer Car that regulated by Bina Marga No. 001 / T / BNKT / 1990. The result of the calculation of travel time with this method will show the actual travel time of the vehicle on Pekanbaru - Bangkinang Km. 19 to Km. 25. This method is classified into Direct Method to determining the travel time. Moving Observer Car method using test equipment in the form of cars with the number of 8 units. The average travel time of the vehicle obtained from the results of data for 8 units of test cars is 7,364 minutes.Keywords:Travel time estimation, Direct Method, Moving Observer car